Work–Life Enrichment and Interference Among Swedish Workers: Trends From 2016 Until the COVID-19 Pandemic - Brulin, Emma; Leineweber, Constanze; Peristera, Paraskevi (Frontiers in Psychology, 2022)
The COVID-19 pandemic has altered workers' possibilities to combine work and private life. Work and private life could either interfere with each other, i.e., when conflict demands arise, or enrich, i.e., when the two roles are beneficial to one another. Analyzing data from the Swedish Longitudinal Occupational Survey of Health through individual growth models, we investigated time trends of interference and enrichment between work and private life from 2016 through March to September 2020, which is during the first wave of the pandemic. The sample included workers who had remained in the same workplace throughout the studied period and worked at least 30% of full time, reaching 5465 individuals. In addition, we examined trends of interference and enrichment across gender and industries. Life-to-work interference increased over time in the Swedish working population, but neither did work-to-life interference nor enrichment. We observed only marginal differences across gender. Also, in the industries of fine manufacturing and real estate activities, a decrease in interference and work-to-life interference and life-to-work interference, respectively, was observed. In the human health and social care industry, an increase in interference and life-to-work interference was seen. Our conclusions are that overall changes to the possibilities to balance work and private life have occurred for workers in Sweden during the first period of the pandemic. Further studies are needed to study development time trends throughout the pandemic and across different occupations.